Protective film for all-solid-state battery
By using a protective film of hydrogen sulfide adsorption material in an all-solid state battery to cover the heat sealing part of the battery, the problem of hydrogen sulfide release is solved and the safety and performance of the battery is improved.
Patent Information
- Application Number
- CN202380044665.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-30
- Filing Date
- 2023-06-21
- Publication Date
- 2025-01-14
AI Technical Summary
In all-solid state batteries using sulfide-based solid electrolytes, hydrogen sulfide (H2S) is easily generated, resulting in its release to the external environment and affecting safety.
A full-solid battery protective film containing hydrogen sulfide adsorption material is used to suppress the release of hydrogen sulfide by covering the heat sealing portion of the battery. The protective film may have a multi-layer structure, including a substrate film, an adhesive layer and a gas barrier layer, and the adhesive layer or substrate film contains a mixture of hydrogen sulfide adsorption materials such as zinc oxide, zeolite or copper oxide.
Effectively inhibit the release of hydrogen sulfide to the external environment, improving the safety and performance of the battery.
Smart Images

Figure CN119318062A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a protective film for an all-solid-state battery. Background Art
[0002] Secondary batteries such as lithium-ion batteries are widely used in portable electronic devices, electric vehicles and hybrid electric vehicles powered by electricity. As a battery that improves the safety of lithium-ion batteries, all-solid-state lithium batteries that use inorganic solid electrolytes instead of organic solvent electrolytes are being studied. All-solid-state lithium batteries are safer than lithium-ion batteries in that they are less likely to experience thermal runaway due to short circuits, etc.
[0003] Among inorganic solid electrolytes, sulfide-based solid electrolytes have higher ionic conductivity than oxide-based solid electrolytes, and have many advantages in obtaining higher-performance all-solid-state batteries. For example, Patent Document 1 discloses an all-solid-state battery using a sulfide-based electrolyte powder containing sulfur, lithium, and at least one element selected from the group consisting of boron, silicon, germanium, phosphorus, and aluminum, and having an average particle size of 0.01 to 10 μm.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2008-288098 Summary of the invention
[0007] Problems to be solved by the invention
[0008] In an all-solid-state battery using a sulfide-based solid electrolyte, hydrogen sulfide (H2S) may be generated. Therefore, an object of the present invention is to provide a protective film for an all-solid-state battery that can suppress the release of hydrogen sulfide to the external environment.
[0009] Means for solving problems
[0010] The present invention relates to a protective film for an all-solid-state battery, which is a protective film arranged in a manner to cover a heat-sealed portion of an all-solid-state battery, wherein the all-solid-state battery comprises: a battery element having a solid electrolyte, a packaging material accommodating the battery element, and the heat-sealed portion provided at the peripheral portion of the packaging material, wherein the protective film contains a hydrogen sulfide adsorbing material. According to such a protective film for an all-solid-state battery, the release of hydrogen sulfide to the external environment can be suppressed.
[0011] The above-mentioned protective film for all-solid-state batteries may have a multilayer structure including a substrate film and an adhesive layer, and the hydrogen sulfide adsorption material is contained in at least one of the substrate film and the adhesive layer. The above-mentioned protective film for all-solid-state batteries may also include a gas barrier layer arranged on at least one surface of the substrate film. The above-mentioned gas barrier layer may contain at least one of aluminum oxide and silicon dioxide. The water vapor permeability of the above-mentioned protective film for all-solid-state batteries is preferably 10g / m 2 · Below the day.
[0012] The all-solid-state battery protective film may have a multi-layer structure including a metal foil and an adhesive layer, and the adhesive layer may contain the hydrogen sulfide adsorbent.
[0013] The hydrogen sulfide adsorbent may contain zinc oxide; may be zeolite containing zinc ions; may be a mixture containing zeolite, zinc oxide, and copper oxide; or may contain at least one of silver sulfate and silver acetate.
[0014] Effects of the Invention
[0015] According to the present invention, there is provided a protective film for an all-solid-state battery capable of suppressing the release of hydrogen sulfide to the external environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] [ Figure 1 ] is a perspective view showing an example of an all-solid-state battery having a protective film for an all-solid-state battery involved in the present embodiment.
[0017] [ Figure 2 ]yes Figure 1 A cross-sectional view along line II-II is shown.
[0018] [ Figure 3 ] is a schematic cross-sectional view of a protective film for an all-solid-state battery according to one embodiment of the present invention.
[0019] [ Figure 4 ] is a schematic cross-sectional view of a protective film for an all-solid-state battery according to one embodiment of the present invention.
[0020] [ Figure 5 ] is a schematic cross-sectional view of a protective film for an all-solid-state battery according to one embodiment of the present invention. DETAILED DESCRIPTION
[0021] Hereinafter, the embodiments of the present invention will be described in detail with reference to the accompanying drawings as appropriate. It should be noted that in the accompanying drawings, the same or corresponding parts are marked with the same symbols, and repeated descriptions are omitted. In addition, the dimensional ratios of the accompanying drawings are not limited to the ratios shown in the drawings.
[0022] The protective film for an all-solid-state battery involved in this embodiment is a protective film arranged in a manner covering a heat-sealed portion of an all-solid-state battery, wherein the all-solid-state battery comprises: a battery element having a solid electrolyte, a packaging material for accommodating the battery element, and a heat-sealed portion provided at the peripheral portion of the packaging material, and the protective film contains a hydrogen sulfide adsorbing material. With such a protective film, the release of hydrogen sulfide to the external environment can be suppressed.
[0023] Figure 1 This is a perspective view showing an example of an all-solid-state battery including the all-solid-state battery protective film according to the present embodiment. Figure 2 yes Figure 1 The cross-sectional view of the II-II line shown in the figures. The all-solid-state battery 50 shown in these figures comprises: a battery element 52 having a solid electrolyte, a packaging material 10 for accommodating the battery element 52, two metal terminals (current output terminals) 53 for outputting current from the battery element 52 to the outside, and a protective film (protective film for all-solid-state battery) 20. The packaging material 10 is obtained, for example, by heat-sealing a laminated film having a substrate layer and a sealing layer. For the packaging material 10, for example, in a manner such that the substrate layer becomes the external side of the all-solid-state battery 50 and the sealing layer becomes the internal side of the all-solid-state battery 50, a laminated film is folded in half and the peripheral portion is heat-fused, or two laminated films are overlapped and the peripheral portions are heat-fused, thereby forming a structure in which a heat-sealed portion is provided at the peripheral portion and the battery element 52 is contained inside. The protective film 20 is configured in a manner that covers the heat-sealed portion provided at the peripheral portion of the packaging material 10.
[0024] The battery element 52 is formed by sandwiching a sulfide-based solid electrolyte between a positive electrode and a negative electrode. The metal terminal 53 is formed by a part of the collector extending outside the packaging material 10, and is composed of a metal foil such as copper foil or aluminum foil. The metal terminal 53 is clamped and sealed by the packaging material 10 forming a container. The metal terminal 53 can also be clamped by the packaging material 10 via a tab seal.
[0025] The protective film 20 contains a hydrogen sulfide adsorbent. A hydrogen sulfide adsorbent refers to a substance that can adsorb and / or decompose hydrogen sulfide. Examples of hydrogen sulfide adsorbents include zinc oxide, amorphous metal silicates (mainly amorphous metal silicates with copper and zinc as the metal), hydrates of zirconium / lanthanide elements, tetravalent metal phosphates (especially phosphates with copper as the metal), zeolites containing zinc ions, mixtures containing zeolites, zinc oxide and copper oxide (such as copper (II) oxide), potassium permanganate, sodium permanganate, silver sulfate, silver acetate, aluminum oxide, iron hydroxide, aluminum silicate, potassium aluminum sulfate, zeolites, hydrotalcites, composite oxides (mainly composite oxides with zinc as the metal), activated carbon, amine compounds, ionomers, and the like. From the perspective of making it easier to render hydrogen sulfide harmless, cost, and operability, the hydrogen sulfide adsorbent may contain zinc oxide (ZnO) and / or zinc ions. The hydrogen sulfide adsorbent may be used alone or in combination of two or more.
[0026] As the hydrogen sulfide adsorbing material, a deodorant having a deodorizing effect on hydrogen sulfide may also be used. Specifically, examples thereof include: "Daimushu PE-M 3000-Z" manufactured by Dainichi Seika Industries Co., Ltd. (a material composed of three components: ZnO, CaO, and potassium aluminum sulfate), "Kesumon" series manufactured by Toagosei Co., Ltd., "Shu-Cleanse" manufactured by Rasa Industries, Ltd. (a mixture of zeolite and zinc oxide), "Dushlite ZU" manufactured by Sinanen Zeomic Co., Ltd. (a mixture of zeolite and zinc), "Dushlite CZU" (a mixture of zeolite, copper oxide, and zinc oxide), and "Dushlite ZH" (a zeolite containing zinc ions).
[0027] From the viewpoint of easily obtaining excellent hydrogen sulfide absorbency, the hydrogen sulfide adsorbent is preferably a material containing zinc oxide; a zeolite containing zinc ions; a mixture containing zeolite, zinc oxide, and copper oxide; and a material containing at least one of silver sulfate and silver acetate.
[0028] From the viewpoint of easily obtaining excellent hydrogen sulfide absorption, the average particle size (D50) of the hydrogen sulfide adsorbent may be 0.01 μm or more, 0.05 μm or more, or 0.1 μm or more. From the viewpoint of improving dispersibility, the average particle size (D50) of the hydrogen sulfide adsorbent may be 5 μm or less, and from the viewpoint of increasing the specific surface area and improving the hydrogen sulfide adsorption performance, it may be 4 μm or less, 3 μm or less, or 2 μm or less. The average particle size of the hydrogen sulfide adsorbent refers to the average particle size measured by the dynamic light scattering method.
[0029] The water vapor permeability of the protective film 20 is preferably 10 g / m 2Less than 1 day, more preferably 0.1 g / m 2 ·Days or less, more preferably 0.01 g / m 2 The water vapor permeability of the protective film 20 can be, for example, 0 g / m 2 ·Day, can also exceed 0g / m 2 ·sky.
[0030] In this specification, the water vapor permeability refers to the water vapor permeability at 40°C and 90%RH measured according to "JIS Z 0208:1976 cup method". It is believed that hydrogen sulfide is generated by the reaction of water that penetrates into the interior of the all-solid-state battery with the sulfur component of the all-solid-state battery. That is, according to the protective film 20 having the above water vapor permeability, it is believed that it is easy to suppress the generation of hydrogen sulfide itself.
[0031] The thickness of the protective film 20 is not particularly limited, and may be, for example, in the range of 3 to 200 μm, 5 to 100 μm, or 20 to 80 μm.
[0032] Hereinafter, a specific example of the protective film 20 will be described further. Figure 3 This is a schematic cross-sectional view of a protective film for an all-solid-state battery according to one embodiment of the present invention. Figure 3 The protective film 20 shown includes a base film 1 , a gas barrier layer 1 a , and an adhesive layer 3 in this order.
[0033] The gas barrier layer 1a has a water vapor barrier property that prevents moisture from penetrating into the interior of the all-solid-state battery. The gas barrier layer 1a may or may not be present, but by providing the gas barrier layer 1a on at least one surface of the substrate film 1, the protective film can be given a water vapor barrier property that prevents moisture from penetrating into the interior of the all-solid-state battery.
[0034] The gas barrier layer 1a may be, for example, a metal vapor-deposited layer, an inorganic oxide vapor-deposited layer, a carbon-containing inorganic oxide vapor-deposited layer, or the like. The gas barrier layer 1a preferably contains, for example, at least one of aluminum oxide and silicon dioxide.
[0035] The substrate film 1 is preferably a film formed of an insulating resin. As the resin, polyester resin, polyamide resin, polyimide resin, polyamideimide resin, polyetherketone resin, polyphenylene sulfide resin, polyetherimide resin, polysulfone resin, fluororesin, phenolic resin, melamine resin, urethane resin, allyl resin, silicone resin, epoxy resin, furan resin, acetyl cellulose resin, etc. can be used.
[0036] The substrate film 1 may be a single layer or a multilayer, and in the case of a multilayer, different resins may be combined to form the substrate film 1. In the case of a multilayer film, the substrate film 1 may be a coextruded film or a film laminated via an adhesive.
[0037] Among these resins, polyester resin or polyamide resin is preferred as the base film 1. Examples of the polyester resin include polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate. Examples of the polyamide resin constituting the polyamide film include nylon 6, nylon 6,6, a copolymer of nylon 6 and nylon 6,6, nylon 6, nylon 9T, nylon 10, poly(m-xylylene adipamide) (MXD6), nylon 11, and nylon 12.
[0038] The substrate film 1 is preferably a biaxially stretched film. As the stretching method of the biaxially stretched film, for example, a sequential biaxial stretching method, a tubular biaxial stretching method, a simultaneous biaxial stretching method, etc. can be cited. From the viewpoint of obtaining a more excellent deep drawing formability, the biaxially stretched film is preferably a film stretched by a tubular biaxial stretching method.
[0039] When the adhesive layer 3 is a sealing layer described below, the melting point peak temperature of the base film 1 is preferably higher than the melting point peak temperature of the sealing layer, more preferably 30° C. or more higher than the melting point peak temperature of the sealing layer, from the viewpoint of suppressing deformation of the base film 1 during sealing.
[0040] The thickness of the base film 1 is preferably 1 to 40 μm, more preferably 2 to 30 μm, and even more preferably 3 to 20 μm.
[0041] The adhesive layer 3 is a layer for bonding the protective film 20 to the sealing material 10. Examples of the adhesive layer 3 include an adhesive layer formed of an adhesive, an adhesive layer formed of an adhesive, and a sealing layer formed of a sealing material.
[0042] As the adhesive, for example, there can be listed: polyurethane resin formed by allowing a bifunctional or higher isocyanate compound (multifunctional isocyanate compound) to act on a main agent such as polyester polyol, polyether polyol, acrylic polyol, carbonate polyol, etc.; and epoxy resin formed by allowing an amine compound or the like to act on a main agent having an epoxy group, etc. From the viewpoint of heat resistance, the adhesive preferably contains an epoxy resin.
[0043] The thickness of the adhesive layer is not particularly limited, but may be, for example, 1 to 10 μm, or 2 to 7 μm, from the viewpoint of adhesive strength, followability, and the like.
[0044] As the adhesive, any adhesive that can bond to the packaging material can be used as appropriate. Examples of the adhesive include acrylic adhesives and silicone adhesives. From the viewpoint of heat resistance, the adhesive is preferably a silicone adhesive.
[0045] The thickness of the pressure-sensitive adhesive layer is not particularly limited, but may be, for example, 1 to 10 μm, or 2 to 7 μm, from the viewpoint of adhesive strength, followability, and the like.
[0046] The sealing layer is a layer that imparts sealing properties to the protective film 20 by heat sealing. Examples of the material constituting the sealing layer include thermoplastic resins such as polyolefin resins, polyamide resins, polyester resins, polycarbonate resins, polyphenylene ether resins, polyacetal resins, polystyrene resins, polyvinyl chloride resins, and polyvinyl acetate resins.
[0047] From the viewpoint of heat resistance and sealing adaptability, the main component of the sealing layer (hereinafter also referred to as "base resin") is preferably one selected from the group consisting of polyolefin resins, polyamide resins and polyester resins. The various resins listed above can be used alone or in combination of two or more. By mixing the various resins listed above and forming a polymer alloy, the sealing adaptability and heat resistance can be controlled.
[0048] Examples of polyolefin resins include low-density, medium-density or high-density polyethylene; ethylene-α-olefin copolymers; polypropylene; block or random copolymers containing propylene as a copolymer component; and propylene-α-olefin copolymers. When the polyolefin resin is a copolymer, it may be a block copolymer or a random copolymer.
[0049] Examples of the polyester resin include polyethylene terephthalate (PET) resin, polybutylene terephthalate (PBT) resin, polyethylene naphthalate (PEN) resin, polybutylene naphthalate (PBN) resin, and copolymers thereof. The polyester resin may be a resin obtained by copolymerizing any acid and diol.
[0050] The sealing layer may contain a polyolefin elastomer. The polyolefin elastomer may be compatible with the above-mentioned base resin, or may not be compatible, and may contain both a compatible polyolefin elastomer and an incompatible polyolefin elastomer. Compatibility (compatible system) means that the elastomer is dispersed in the base resin in a manner such that the dispersed phase size is greater than 1 nm and less than 500 nm. Incompatibility (incompatible system) means that the elastomer is dispersed in the base resin in a manner such that the dispersed phase size is greater than 500 nm and less than 20 μm.
[0051] When the base resin is a polypropylene resin, examples of compatible polyolefin elastomers include propylene-butene-1 random copolymers, and examples of incompatible polyolefin elastomers include ethylene-butene-1 random copolymers. The polyolefin elastomers may be used alone or in combination of two or more.
[0052] In addition, in order to impart sealing properties, heat resistance and other functionalities, the sealing layer may contain, for example, antioxidants, slip agents, flame retardants, anti-blocking agents, light stabilizers, dehydrating agents, tackifiers, crystal nucleating agents, and plasticizers as additives. When the total mass of the sealing layer is set to 100 parts by mass, the content of these additives is preferably 5 parts by mass or less.
[0053] The melting peak temperature of the sealant layer varies depending on the application, but from the viewpoint of heat resistance, it may be, for example, 160 to 280° C. The thickness of the sealant layer is not particularly limited, but from the viewpoint of thin film and heat seal strength, it may be, for example, 10 to 200 μm, or 20 to 150 μm. In the case where the sealant layer is multi-layered, the total thickness of the plurality of sealants may be within the above range, or the thickness of each of the plurality of sealants may be within the above range.
[0054] At least one of the base film 1 and the adhesive layer 3 contains a hydrogen sulfide adsorbent.
[0055] From the viewpoint of easily obtaining excellent hydrogen sulfide absorption, the content of the hydrogen sulfide adsorbent in the substrate film 1 may be 0.5 mass % or more, 1 mass % or more, 2 mass % or more, 3 mass % or more, or 4 mass % or more, based on the total mass of the substrate film 1. The content of the hydrogen sulfide adsorbent may be 50 mass % or less, 40 mass % or less, 30 mass % or less, 20 mass % or less, 10 mass % or less, or 0 mass % based on the total mass of the substrate film 1. The content of the hydrogen sulfide adsorbent may be 0 to 50 mass %, 0.5 to 50 mass %, 1 to 40 mass %, 2 to 30 mass %, 3 to 20 mass %, or 4 to 10 mass % based on the total mass of the substrate film 1.
[0056] From the viewpoint of easily obtaining excellent hydrogen sulfide absorption, the content of the hydrogen sulfide adsorbent in the adhesive layer 3 may be 0.5 mass % or more, 1 mass % or more, 2 mass % or more, 3 mass % or more, or 4 mass % or more, based on the total mass of the adhesive layer 3. From the viewpoint of adhesion, the content of the hydrogen sulfide adsorbent may be 50 mass % or less, 40 mass % or less, 30 mass % or less, 20 mass % or less, 10 mass % or less, or 0 mass % based on the total mass of the adhesive layer 3. The content of the hydrogen sulfide adsorbent may be 0 to 50 mass %, 0.5 to 50 mass %, 1 to 40 mass %, 2 to 30 mass %, 3 to 20 mass %, or 4 to 10 mass % based on the total mass of the adhesive layer 3.
[0057] Figure 3The protective film 20 shown has a multi-layer structure including a base film 1 and an adhesive layer 3, and the hydrogen sulfide adsorbent is contained in at least one of the base film 1 and the adhesive layer 3. Such a protective film is believed to be able to effectively suppress the release of hydrogen sulfide to the external environment.
[0058] Figure 3 The protective film 20 shown can be produced, for example, by a method including the steps of forming the gas barrier layer 1 a on one surface of the base film 1 and forming the adhesive layer 3 on the gas barrier layer 1 a .
[0059] The gas barrier layer 1a can be formed, for example, by attaching a constituent material of the gas barrier layer 1a to one surface of the base film 1. When the gas barrier layer 1a is a metal vapor-deposited layer, for example, metal may be vapor-deposited on one surface of the base film 1.
[0060] The adhesive layer 3 can be formed, for example, by coating a composition containing an adhesive or a binder on the gas barrier layer 1a; or by forming a film of a composition containing components constituting a sealing layer using an extruder such as a T-die and then adhering it to the gas barrier layer 1a using an adhesive or heat fusion.
[0061] An example of the protective film and the method for producing the same has been described above, but the present invention is not limited to this specific embodiment, and various modifications and changes can be made within the scope of the gist of the present invention described in the claims.
[0062] For example, the positional relationship between the base film 1 and the gas barrier layer 1a may be reversed. Figure 4 The protective film 30 shown in FIG. 1 includes a gas barrier layer 1a, a base film 1, and an adhesive layer 3 in this order. The gas barrier layer 1a may be provided on both surfaces of the base film 1.
[0063] Figure 4 The protective film 30 shown can be manufactured, for example, by a process including forming a gas barrier layer 1a on one surface of a substrate film 1; and forming an adhesive layer 3 on the surface of the substrate film 1 opposite to the gas barrier layer 1a. The gas barrier layer 1a can be formed, for example, in the same manner as described above. The adhesive layer 3 can be formed, for example, by coating a composition containing an adhesive or a bonding agent on the surface of the substrate film 1 opposite to the gas barrier layer 1a; or by forming a film of a composition containing components constituting a sealing layer using an extruder such as a T-die, and then attaching it to the surface of the substrate film 1 opposite to the gas barrier layer 1a using an adhesive or heat fusion.
[0064] The protective film may have a multi-layer structure including a metal foil and an adhesive layer, and the adhesive layer may contain a hydrogen sulfide adsorbent. Figure 5 An example of such a protective film is shown.
[0065] Figure 5The protective film 40 shown has a structure in which a metal foil 2 and an adhesive layer 3 are stacked.
[0066] The metal foil 2 has a water vapor barrier property that prevents water from penetrating into the interior of the all-solid-state battery. Examples of metals constituting the metal foil 2 include aluminum, stainless steel, and copper. The metal foil 2 may contain, for example, at least one metal selected from the group consisting of aluminum, stainless steel, and copper. From the perspective of moisture resistance, processability, and cost, the metal foil 2 is preferably aluminum foil.
[0067] As aluminum foil, from the perspective of being able to impart the desired ductility during molding, it is particularly preferred to use a soft aluminum foil that has been annealed, but in order to further impart pinhole resistance and ductility during molding, an iron-containing aluminum foil may also be used. In 100% by mass of aluminum foil, the iron content in the aluminum foil is preferably 0.1 to 9.0% by mass, more preferably 0.5 to 2.0% by mass. By making the iron content 0.1% or more by mass, a protective film 40 having excellent pinhole resistance and ductility can be obtained. By making the iron content 9.0% or less by mass, a protective film 40 with better softness can be obtained. As aluminum foil, untreated aluminum foil can be used, but from the perspective of imparting corrosion resistance, it is preferred to use aluminum foil that has been degreased. When degreasing the aluminum foil, degreasing may be performed only on one side of the aluminum foil, or degreasing may be performed on both sides.
[0068] The thickness of the metal foil 2 is preferably 1 to 100 μm, more preferably 5 to 80 μm, and even more preferably 10 to 60 μm.
[0069] The adhesive layer 3 may be, for example, the above-mentioned adhesive layer, pressure-sensitive adhesive layer, or sealant layer. From the viewpoint of adhesion to aluminum foil, etc., the sealant layer may contain acid-modified polypropylene.
[0070] In the protective film 40, the adhesive layer 3 contains a hydrogen sulfide adsorbent. From the viewpoint of easily obtaining excellent hydrogen sulfide absorption, the content of the hydrogen sulfide adsorbent can be 0.1% by mass or more, 0.3% by mass or more, 0.5% by mass or more, 1% by mass or more, or 2% by mass or more, based on the total mass of the adhesive layer 3. From the viewpoint of adhesion, the content of the hydrogen sulfide adsorbent can be 50% by mass or less, 40% by mass or less, 30% by mass or less, 20% by mass or less, or 10% by mass or less, based on the total mass of the adhesive layer 3. The content of the hydrogen sulfide adsorbent can be 0.1 to 50% by mass, 0.3 to 40% by mass, 0.5 to 30% by mass, 1 to 20% by mass, or 2 to 10% by mass, based on the total mass of the adhesive layer 3.
[0071] Figure 5The protective film 40 shown can be manufactured, for example, by a method including a step of forming an adhesive layer 3 on one surface of a metal foil 2. The adhesive layer 3 can be formed, for example, by coating a composition containing an adhesive or a bonding agent on the metal foil 2; or by forming a film of a composition containing components constituting a sealing layer using an extruder such as a T-die, and then attaching the film to the metal foil 2 using an adhesive or heat fusion.
[0072] The present disclosure relates to the following matters.
[0073] [1] A protective film for an all-solid-state battery, the protective film being arranged in a manner to cover a heat-sealed portion of the all-solid-state battery, the all-solid-state battery comprising: a battery element having a solid electrolyte, a packaging material accommodating the battery element, and the heat-sealed portion provided at a peripheral portion of the packaging material, the protective film containing a hydrogen sulfide adsorbent.
[0074] [2] The all-solid-state battery protective film according to [1], having a multilayer structure including a base film and an adhesive layer, wherein the hydrogen sulfide adsorbent is contained in at least one of the base film and the adhesive layer.
[0075] [3] The all-solid-state battery protective film according to [2], further comprising a gas barrier layer provided on at least one surface of the base film.
[0076] [4] The all-solid-state battery protective film according to [1], having a multilayer structure including a metal foil and an adhesive layer, wherein the adhesive layer contains the hydrogen sulfide adsorbent.
[0077] [5] The all-solid-state battery protective film according to any one of [1] to [4], wherein the hydrogen sulfide adsorbent contains zinc oxide.
[0078] [6] The all-solid-state battery protective film according to any one of [1] to [4], wherein the hydrogen sulfide adsorbent is a zeolite containing zinc ions.
[0079] [7] The all-solid-state battery protective film according to any one of [1] to [4], wherein the hydrogen sulfide adsorbent is a mixture containing zeolite, zinc oxide, and copper oxide.
[0080] [8] The all-solid-state battery protective film according to any one of [1] to [4], wherein the hydrogen sulfide adsorbent contains at least one of silver sulfate and silver acetate.
[0081] [9] The all-solid-state battery protective film according to [3], wherein the gas barrier layer contains at least one of aluminum oxide and silicon dioxide.
[0082]
[10] The all-solid-state battery protective film according to any one of [1] to [9], wherein the water vapor permeability is 10 g / m 2 · Below the day.
[0083] Example
[0084] Hereinafter, the present invention will be described in more detail based on Examples, but the present invention is not limited to the following Examples.
[0085] [Materials used]
[0086] The materials used in Examples and Comparative Examples are as follows.
[0087] <Base Film Forming Resin>
[0088] Polyethylene terephthalate (PET)
[0089] <Metal foil (thickness 50 μm)>
[0090] An annealed and degreased soft aluminum foil ("8079 material" manufactured by Toyo Aluminum KK) was used.
[0091] <Composition for forming adhesive layer (adhesive layer, pressure-sensitive adhesive layer or sealant layer)>
[0092] (Adhesive)
[0093] Araldite (registered trademark) (manufactured by HUNTSMAN Advanced Materials, a two-component epoxy adhesive) was used.
[0094] (Adhesive)
[0095] Use acrylic PSA tape.
[0096] (Sealant layer forming composition)
[0097] TSA16 manufactured by Toray Industries, Inc. was used.
[0098] <Hydrogen sulfide adsorbent>
[0099] Material A: manufactured by Sinanen Zeomic Co., Ltd., trade name Dushlite ZH (zeolite containing zinc ions)
[0100] Material B: manufactured by Dainichi Seika Industries, Ltd., trade name "Daimushu PE-M3000-Z" (a material composed of three components: ZnO, CaO, and potassium aluminum sulfate)
[0101] [Production of protective film]
[0102] (Example 1)
[0103] As a substrate film, a polyethylene terephthalate (PET) film (thickness 12 μm) containing 5.0 mass % of the hydrogen sulfide adsorbent material A was prepared. Alumina was deposited on one surface of the obtained film to prepare a gas barrier film having a metal deposition layer and a substrate film.
[0104] (Example 2)
[0105] As a substrate film, a polyethylene terephthalate (PET) film (thickness 12 μm) containing 5.0 mass % of material A, which is a hydrogen sulfide adsorbing material, was prepared. Aluminum oxide was vapor-deposited on one surface of the obtained film to prepare a gas barrier film having a metal vapor-deposited layer and a substrate film. Next, a sealing layer was formed on the surface of the gas barrier film on the metal vapor-deposited layer side to prepare a protective film having a substrate film, a metal vapor-deposited layer, and a sealing layer in this order.
[0106] (Example 3)
[0107] As a substrate film, a polyethylene terephthalate (PET) film (thickness 12 μm) containing 5.0 mass % of the hydrogen sulfide adsorbing material A was prepared. A gas barrier film having a metal vapor-deposited layer and a substrate film was prepared by vapor-depositing aluminum oxide on one surface of the obtained film. Next, an adhesive was applied to the surface of the gas barrier film on the metal vapor-deposited layer side to form an adhesive layer, thereby preparing a protective film having a substrate film, a metal vapor-deposited layer, and an adhesive layer in this order.
[0108] (Example 4)
[0109] As a substrate film, a polyethylene terephthalate (PET) film (thickness 12 μm) containing 5.0% by mass of the hydrogen sulfide adsorbing material A was prepared. A gas barrier film having a metal vapor-deposited layer and a substrate film was prepared by vapor-depositing aluminum oxide on one surface of the obtained film. Next, an adhesive was applied to the surface of the gas barrier film on the metal vapor-deposited layer side to form an adhesive layer, thereby preparing a protective film having a substrate film, a metal vapor-deposited layer, and an adhesive layer in this order.
[0110] (Example 5)
[0111] A polyethylene terephthalate (PET) film (thickness 12 μm) was prepared as a substrate film. A gas barrier film having a metal vapor-deposited layer and a substrate film was prepared by vapor-depositing aluminum oxide on one surface of the obtained film. Next, a sealing layer containing 5.0 mass % of a hydrogen sulfide adsorbing material of material A was formed on the surface of the gas barrier film on the metal vapor-deposited layer side, thereby preparing a protective film having a substrate film, a metal vapor-deposited layer, and a sealing layer in sequence.
[0112] (Example 6)
[0113] A polyethylene terephthalate (PET) film (thickness 12 μm) was prepared as a substrate film. A gas barrier film having a metal vapor-deposited layer and a substrate film was prepared by vapor-depositing aluminum oxide on one surface of the obtained film. Next, a sealing layer containing 2.5% by mass of a hydrogen sulfide adsorbing material of material A was formed on the surface of the gas barrier film on the metal vapor-deposited layer side, thereby preparing a protective film having a substrate film, a metal vapor-deposited layer, and a sealing layer in this order.
[0114] (Example 7)
[0115] A polyethylene terephthalate (PET) film (thickness 12 μm) was prepared as a substrate film. A gas barrier film having a metal vapor-deposited layer and a substrate film was prepared by vapor-depositing aluminum oxide on one surface of the obtained film. Next, a sealing layer containing 30.0% by mass of a hydrogen sulfide adsorbing material of material A was formed on the surface of the gas barrier film on the metal vapor-deposited layer side, thereby preparing a protective film having a substrate film, a metal vapor-deposited layer, and a sealing layer in sequence.
[0116] (Example 8)
[0117] A polyethylene terephthalate (PET) film (thickness 12 μm) was prepared as a substrate film. A gas barrier film having a metal vapor-deposited layer and a substrate film was prepared by vapor-depositing aluminum oxide on one surface of the obtained film. Next, a sealing layer containing 5.0% by mass of a hydrogen sulfide adsorbing material of material B was formed on the surface of the gas barrier film on the metal vapor-deposited layer side, thereby preparing a protective film having a substrate film, a metal vapor-deposited layer, and a sealing layer in sequence.
[0118] (Example 9)
[0119] A polyethylene terephthalate (PET) film (thickness 12 μm) was prepared as a substrate film. A gas barrier film having a metal vapor-deposited layer and a substrate film was prepared by vapor-depositing aluminum oxide on one surface of the obtained film. Next, an adhesive layer containing 5.0% by mass of a hydrogen sulfide adsorbing material of Material A was formed on the surface of the gas barrier film on the metal vapor-deposited layer side, thereby preparing a protective film having a substrate film, a metal vapor-deposited layer, and an adhesive layer in this order.
[0120] (Example 10)
[0121] A polyethylene terephthalate (PET) film (thickness 12 μm) was prepared as a substrate film. A gas barrier film having a metal vapor-deposited layer and a substrate film was prepared by vapor-depositing aluminum oxide on one surface of the obtained film. Next, an adhesive layer containing 5.0% by mass of a hydrogen sulfide adsorbing material of Material A was formed on the surface of the gas barrier film on the metal vapor-deposited layer side, thereby preparing a protective film having a substrate film, a metal vapor-deposited layer, and an adhesive layer in this order.
[0122] (Example 11)
[0123] As a substrate film, a polyethylene terephthalate (PET) film (thickness 12 μm) containing 5.0% by mass of the hydrogen sulfide adsorbing material of material A was prepared. A gas barrier film having a metal vapor-deposited layer and a substrate film was prepared by vapor-depositing aluminum oxide on one surface of the obtained film. Next, a sealing layer containing 5.0% by mass of the hydrogen sulfide adsorbing material of material A was formed on the surface of the gas barrier film on the metal vapor-deposited layer side, thereby preparing a protective film having a substrate film, a metal vapor-deposited layer, and a sealing layer in this order.
[0124] (Example 12)
[0125] As a substrate film, a polyethylene terephthalate (PET) film (thickness 12 μm) containing 5.0% by mass of the hydrogen sulfide adsorbing material of material A was prepared. A gas barrier film having a metal vapor-deposited layer and a substrate film was prepared by vapor-depositing aluminum oxide on one surface of the obtained film. Next, an adhesive layer containing 5.0% by mass of the hydrogen sulfide adsorbing material of material A was formed on the surface of the gas barrier film on the metal vapor-deposited layer side, thereby preparing a protective film having a substrate film, a metal vapor-deposited layer, and an adhesive layer in this order.
[0126] (Example 13)
[0127] As a substrate film, a polyethylene terephthalate (PET) film (thickness 12 μm) containing 5.0% by mass of the hydrogen sulfide adsorbing material of material A was prepared. A gas barrier film having a metal vapor-deposited layer and a substrate film was prepared by vapor-depositing aluminum oxide on one surface of the obtained film. Next, an adhesive layer containing 5.0% by mass of the hydrogen sulfide adsorbing material of material A was formed on the surface of the gas barrier film on the metal vapor-deposited layer side, thereby preparing a protective film having a substrate film, a metal vapor-deposited layer, and an adhesive layer in this order.
[0128] (Example 14)
[0129] A polyethylene terephthalate (PET) film (thickness 12 μm) of a hydrogen sulfide adsorbent containing 5.0% by mass of the material A was produced.
[0130] (Example 15)
[0131] As a base film, a polyethylene terephthalate (PET) film (thickness 12 μm) containing 5.0 mass % of the hydrogen sulfide adsorbent material A was prepared. A sealant layer was formed on one surface of the obtained film to prepare a protective film (base film / sealant layer).
[0132] (Example 16)
[0133] As a base film, a polyethylene terephthalate (PET) film (thickness 12 μm) containing 5.0 mass % of the hydrogen sulfide adsorbent material A was prepared. An adhesive layer was formed on one surface of the obtained film to prepare a protective film (base film / adhesive layer).
[0134] (Example 17)
[0135] As a base film, a polyethylene terephthalate (PET) film (thickness 12 μm) containing 5.0 mass % of the hydrogen sulfide adsorbent material A was prepared. A pressure-sensitive adhesive layer was formed on one surface of the obtained film to prepare a protective film (base film / pressure-sensitive adhesive layer).
[0136] (Example 18)
[0137] A polyethylene terephthalate (PET) film (thickness 12 μm) was prepared as a base film, and a sealing layer containing 5.0 mass % of the hydrogen sulfide adsorbent of Material A was formed on one surface of the obtained film to prepare a protective film (base film / sealing layer).
[0138] (Example 19)
[0139] A polyethylene terephthalate (PET) film (thickness 12 μm) was prepared as a base film, and an adhesive layer containing 5.0 mass % of the hydrogen sulfide adsorbent of Material A was formed on one surface of the obtained film to prepare a protective film (base film / adhesive layer).
[0140] (Example 20)
[0141] A polyethylene terephthalate (PET) film (thickness 12 μm) was prepared as a base film, and an adhesive layer containing 5.0 mass % of the hydrogen sulfide adsorbent of Material A was formed on one surface of the obtained film to prepare a protective film (base film / adhesive layer).
[0142] (Example 21)
[0143] As a base film, a polyethylene terephthalate (PET) film (thickness 12 μm) containing 3.0 mass % of the hydrogen sulfide adsorbing material of material A was prepared. A sealing layer containing 5.0 mass % of the hydrogen sulfide adsorbing material of material A was formed on one surface of the obtained film, thereby preparing a protective film (base film / sealing layer).
[0144] (Example 22)
[0145] As a base film, a polyethylene terephthalate (PET) film (thickness 12 μm) containing 3.0 mass % of the hydrogen sulfide adsorbing material of material A was prepared. An adhesive layer containing 5.0 mass % of the hydrogen sulfide adsorbing material of material A was formed on one surface of the obtained film, thereby preparing a protective film (base film / adhesive layer).
[0146] (Example 23)
[0147] As a base film, a polyethylene terephthalate (PET) film (thickness 12 μm) containing 3.0 mass % of the hydrogen sulfide adsorbent material of material A was prepared. An adhesive layer containing 5.0 mass % of the hydrogen sulfide adsorbent material of material A was formed on one surface of the obtained film, thereby preparing a protective film (base film / adhesive layer).
[0148] (Comparative Example 1)
[0149] A polyethylene terephthalate (PET) film (thickness: 12 μm) was prepared as a base film, and a sealing layer was formed on one surface of the obtained film to prepare a protective film (base film / sealing layer).
[0150] (Comparative Example 2)
[0151] A polyethylene terephthalate (PET) film (thickness: 4.5 μm) was prepared as a base film, and a sealing layer was formed on one surface of the obtained film to prepare a protective film (base film / sealing layer).
[0152] (Comparative Example 3)
[0153] A polyethylene terephthalate (PET) film (thickness: 50 μm) was prepared as a base film, and a sealing layer was formed on one surface of the obtained film to prepare a protective film (base film / sealing layer).
[0154] (Comparative Example 4)
[0155] A polyethylene terephthalate (PET) film (thickness: 100 μm) was prepared as a base film, and a sealing layer was formed on one surface of the obtained film to prepare a protective film (base film / sealing layer).
[0156] (Comparative Example 5)
[0157] A polyethylene terephthalate (PET) film (thickness: 12 μm) was prepared as a base film, and an adhesive layer was formed on one surface of the obtained film to prepare a protective film (base film / adhesive layer).
[0158] (Comparative Example 6)
[0159] A polyethylene terephthalate (PET) film (thickness: 12 μm) was prepared as a base film, and a pressure-sensitive adhesive layer was formed on one surface of the obtained film to prepare a protective film (base film / pressure-sensitive adhesive layer).
[0160] (Example 24)
[0161] A protective film (AL layer / sealing layer) was prepared by forming a sealing layer containing 3.0 mass % of the hydrogen sulfide adsorbing material of the material A on one surface of an aluminum foil (AL foil).
[0162] (Example 25)
[0163] A protective film (AL layer / adhesive layer) was prepared by forming an adhesive layer containing 3.0 mass % of the hydrogen sulfide adsorbent of the material A on one surface of an aluminum foil (AL foil).
[0164] (Example 26)
[0165] A protective film (AL layer / adhesive layer) was prepared by forming an adhesive layer containing 3.0 mass % of the hydrogen sulfide adsorbent of Material A on one surface of an aluminum foil (AL foil).
[0166] (Comparative Example 7)
[0167] A protective film (AL layer / adhesive layer) was prepared by forming an adhesive layer on one surface of an aluminum foil (AL foil).
[0168] (Comparative Example 8)
[0169] A protective film (AL layer / adhesive layer) was prepared by forming an adhesive layer on one surface of an aluminum foil (AL foil).
[0170] (Comparative Example 9)
[0171] A protective film (AL layer / adhesive layer) was prepared by forming an adhesive layer on one surface of an aluminum foil (AL foil).
[0172] [Measurement of water vapor transmission rate]
[0173] The water vapor permeability of the gas barrier films of Examples 1 to 17, the substrate films of Examples 14 to 23 and Comparative Examples 1 to 6, and the aluminum foils of Examples 24 to 26 and Comparative Examples 7 to 9 was measured at 40° C. and 90% RH according to “JIS Z0208:1976 cup method”.
[0174] [Evaluation of protective film]
[0175] (Evaluation of hydrogen sulfide (H2S) absorption)
[0176] Cut the protective film into a size of 50 mm x 50 mm as a sample for evaluating hydrogen sulfide absorption. Put the sample into a 2L Tedlar bag and seal the Tedlar bag. Flow 2L of hydrogen sulfide gas with a concentration of 20 mass ppm into the Tedlar bag and leave it at room temperature (25°C) for 144 hours. Measure the hydrogen sulfide concentration in the Tedlar bag after leaving it for 144 hours. Based on the obtained results, evaluate the hydrogen sulfide absorption based on the following evaluation criteria.
[0177] A: Hydrogen sulfide concentration is 5 mass ppm or less
[0178] B: Hydrogen sulfide concentration exceeds 5 mass ppm
[0179] (Peel strength (N / 5mm))
[0180] The protective film is cut into 5 mm wide as a measurement sample. On the other hand, a packaging material for all-solid-state batteries laminated with a PET film as a support is prepared. After the adhesive layer of the obtained measurement sample is arranged on the support in a direction in contact with the support, the measurement sample is bonded to the support. Next, the peel strength of the gas barrier film or substrate film and the adhesive layer is measured (180° peeling, peeling speed is 300 mm / min). It should be noted that, in the case where the adhesive layer is an adhesive layer, after the measurement sample is arranged on the support, a 2kg roller is moved back and forth 5 times to bond the measurement sample to the support. In the case where the adhesive layer is an adhesive layer, the measurement sample is arranged on the support, and after the 2kg roller is moved back and forth 5 times, the adhesive layer is cured. In the case where the adhesive layer is a sealing layer, in the state where the measurement sample is arranged on the support, heat sealing is performed under the conditions of temperature: 150°C, pressure: 0.98MPa, and time: 150 seconds.
[0181] The configurations and evaluation results of Examples and Comparative Examples are summarized in Tables 1 to 3.
[0182] [Table 1]
[0183]
[0184] [Table 2]
[0185]
[0186] [Table 3]
[0187]
[0188] It is found that the protective film of the example is superior in hydrogen sulfide absorption compared to the protective film of the comparative example. In other words, it is found that the protective film of the example can suppress the release of hydrogen sulfide to the external environment compared to the protective film of the comparative example.
[0189] Explanation of symbols
[0190] 10…Packaging material, 20, 30, 40…Protective film for all-solid-state battery, 1…Base film, 1a…Gas barrier layer, 2…Metal foil, 3…Adhesive layer, 50…All-solid-state battery, 52…Battery element, 53…Metal terminal.
Claims
1. A protective film for an all-solid-state battery, the protective film being arranged so as to cover a heat-sealed portion of the all-solid-state battery, The all-solid-state battery comprises: a battery element having a solid electrolyte, a packaging material for accommodating the battery element, and the heat-sealed portion provided at the peripheral edge of the packaging material. The protective film contains a hydrogen sulfide adsorbing material.
2. The protective film for an all-solid-state battery according to claim 1, It has a multilayer structure including a base film and an adhesive layer, The hydrogen sulfide adsorbing material is contained in at least one of the base film and the adhesive layer.
3. The protective film for an all-solid-state battery according to claim 2, The present invention further includes a gas barrier layer provided on at least one surface of the substrate film.
4. The protective film for an all-solid-state battery according to claim 1, It has a multi-layer structure including a metal foil and an adhesive layer. The hydrogen sulfide adsorbing material is contained in the adhesive layer.
5. The protective film for an all-solid-state battery according to any one of claims 1 to 4, wherein The hydrogen sulfide adsorbent contains zinc oxide.
6. The protective film for an all-solid-state battery according to any one of claims 1 to 4, wherein The hydrogen sulfide adsorbing material is zeolite containing zinc ions.
7. The protective film for an all-solid-state battery according to any one of claims 1 to 4, wherein The hydrogen sulfide adsorbing material is a mixture containing zeolite, zinc oxide, and copper oxide.
8. The protective film for an all-solid-state battery according to any one of claims 1 to 4, wherein The hydrogen sulfide adsorbent contains at least one of silver sulfate and silver acetate.
9. The protective film for an all-solid-state battery according to claim 3, wherein: The gas barrier layer contains at least one of aluminum oxide and silicon dioxide.
10. The all-solid-state battery protective film according to any one of claims 1 to 9, wherein the water vapor permeability is 10 g / m 2 · Below the day.
Citation Information
Patent Citations
Sulfide-based electroyte powder, and sulfide-based electroyte molded body using the same
JP2008288098A